Theoretical study on the complexes of benzene with isoelectronic nitrogen-containing heterocycles - Wang, Weizhou; Hobza, Pavel (Chemphyschem, 2008)
The pi-pi interactions between benzene and the aromatic nitrogen heterocycles pyridine, pyrimidine, 1,3,5-triazine, 1,2,3-triazine, 1,2,4,5-tetrazine, and 1,2,3,4,5-pentazine are systematically investigated. The T-shaped structures of all complexes studied exhibit a contraction of the C--H bond accompanied by a rather large blue shift (40-52 cm(-1)) of its stretching frequency, and they are almost isoenergetic with the corresponding displaced-parallel structures at reliable levels of theory. With increasing number of nitrogen atoms in the heterocycle, the geometries, frequencies, energies, percentage of s character at C, and the electron density in the C--H sigma antibonding orbital of the complexes all increase or decrease systematically. Decomposition analysis of the total binding energy showed that for all the complexes, the dispersion energy is the dominant attractive contribution, and a rather large attraction originating from electrostatic contribution is compensated by its exchange counterpart.
Keywords: chemické modely; Electrons; Hydrogen Bonding; Models, Molecular; vodíková vazba; stereoizomerie; Benzene; Models, Chemical; Nitrogen; přenos energie; heterocyklické sloučeniny; elektrony; dusík; molekulární modely; benzen; Energy Transfer; Heterocyclic Compounds; Stereoisomerism